Searching for Experience on the Web: An Empirical Examination of Consumer Behavior for Search and Experience Goods - Huang, Peng; Lurie, Nicholas H.; Mitra, Sabyasachi (Journal of Marketing, 2009)
By lowering the costs of gathering and sharing information and offering new ways to learn about products before purchase, the Internet reduces traditional distinctions between search and experience goods. At the same time, differences in the type of information sought for search and experience goods can precipitate differences in the process through which consumers gather information and make decisions online. A preliminary experiment shows that though there are significant differences in consumers’ perceived ability to evaluate product quality before purchase between search and experience goods in traditional retail environments, these differences are blurred in online environments. An analysis of the online behavior of a representative sample of U.S. consumers shows that consumers spend similar amounts of time online gathering information for both search and experience goods, but there are important differences in the browsing and purchase behavior of consumers for these two types of goods. In particular, experience goods involve greater depth (time per page) and lower breadth (total number of pages) of search than search goods. In addition, free riding (purchasing from a retailer other than the primary source of product information) is less frequent for experience than for search goods. Finally, the presence of product reviews from other consumers and multimedia that enable consumers to interact with products before purchase has a greater effect on consumer search and purchase behavior for experience than for search goods.